At the Sign of the Eagle - Parker, Gilbert, 1862-1932 (Salt Lake City, UT : Project Gutenberg, 2004)
"At the Sign of the Eagle" by Gilbert Parker is a novel written in the early 20th century. The book revolves around the experiences of American businessman John Vandewaters as he navigates social circles in England, where he interacts with the British aristocracy and contemplates the cultural contrasts between America and England. The story likely explores themes of ambition, class disparity, and the personal journey of its protagonist. The narrative follows Vandewaters as he attends a gathering hosted by Sir Duke Lawless and Lady Lawless, where he meets various characters, including the intriguing Gracia Raglan and the obnoxiously privileged Stephen Pride. As Vandewaters becomes embroiled in a possible romantic interest with Gracia, he also faces challenges related to his business affairs, such as sudden financial losses. Through his candid conversations, Vandewaters reveals his rugged past and perspective on wealth and success, leading to a poignant engagement with Gracia that reveals both their vulnerabilities and aspirations. The interplay of social dynamics, class distinctions, and personal integrity forms the crux of the story, providing readers with an exploration of character against the backdrop of early 20th-century society. (This is an automatically generated summary.)
Release date is 2004-11-16
Produced by David Widger
Keywords: Canadian fiction